Website Design at SMK Gema Bangsa - Miftahul Asror, Fathih; Ginting, Novita Br; Jaenudin, Jejen (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2023)
Along with the rapid development of technology, it has an influence on everyday life. Technology was created to facilitate human work. Every year, all educational institutions process school information data. This process is useful for providing information to students and guardians about school activities. Thus, schools need to continue to innovate in improving information services and more comprehensive socialization with student guardians in particular and the community in general. One of them is by utilizing technology and internet media. At SMK Gema Bangsa until now provides school information media that is still conventional using pamphlet media, the delivery of this information is still passive by installing the information media in front of the school gate, and on the side of the road in the school environment. Therefore, to make it easier for schools to provide information to the community, SMK Gema Bangsa utilizes Information Technology, so that in this study a Website will be developed at SMK Gema Bangsa as an information media and can also be used as information socialization.